Cooperation induced by wise incentive allocation in spontaneous institution. (13th September 2016) - Cong, Rui; Li, Kun; Wang, Long; Zhao, Qianchuan
Abstract: Institutional incentives such as punishment and rewarding have recently received wide attention in resolving issues of public goods provision that requires collective cooperation. In this letter, we are interested in exploring the effect on cooperation of a spontaneous institution, which rewards its participants exclusively and also takes the social responsibility of punishing interior and exterior free-riders. Drawing support from evolutionary game theory, our results indicate that the splitting ratio of such institution funds plays a decisive role in determining the evolutionary outcome. Rewarding is essential in sustaining the institution, while a certain intensity of punishment ensures a high overall cooperation level. Our results may provide more insights into understanding the roles institutional incentives play in promoting social cooperation.